Assessing Learning Experiences of Senior Secondary Schools Students in Visual Arts Through Web-Based Instruction Michael Olubunmi ODEWUMI1 Abstract Web, an internet platform, is accessible through technology devices for given information, but its role h: Michael Olubunmi ODEWUMI (PJDOL, 2023)
Web, an internet platform, is accessible through technology devices for given information, but its role has been shifted towards the instructional delivery system. However, its usefulness, utilisation, and importance to learning is yet to be explored. Therefore, the present study investigated the effectiveness of web-based instruction package on the learners' academics performances in visual arts in Nigerian Senior Secondary School.